International immigration and its effects on native labor market: evidence from OECD countries - Mohammad, Reda Abdelfattah; Iman,; Waqar, Shujaa; Attico, Yasir Tageldin Abubaker; Antohi, Valentin Marian; Fortea, Costinela; Zlati, Monica Laura (Frontiers in Human Dynamics, 2025)
This study aims to investigate the impact of international immigration on the native labor market of host countries. With the growing number of cross-border movements, the relationship between immigration and unemployment in the domestic labor market has become a concern for economists and policy makers. This study utilizes the comprehensive dataset of the years spanning from 2000 to 2020 and employs panel regression analysis to analyze the intricate dynamics of international migration and unemployment of native-born workers of 16 selected OECD countries. The results have disclosed a significant negative relationship between net migration rate and unemployment rate of domestic laborers. Furthermore, it was concluded that an increase in GDP, wages and government expenditure on education will significantly reduce the unemployment rate as well. However, the positive relationship of gross national expenditure with the unemployment rate of natives is found to be insignificant. In the light of this negative relationship between net migration rates and native unemployment rates, policy makers should take into account promoting immigration policies internationally that are consistent with economic growth goals. Moreover, investments in GDP growth, wage increases and education expenditure must be made to further reduce unemployment among native born workers.